Morphological and molecular characterization of Udotea species (Bryopsidales, Chlorophyta) from northeastern Brazil with a new record of U. dotyi from the western south Atlantic - C. B. S. ROCHA, MAYARA; B. PEREIRA, SONIA M.; OLIVEIRA-CARVALHO, MARIA F.; BENKO-ISEPPON, ANA M.; F. XIMENES, CAROLINE; T. FUJII, MUTUE; CASSANO, VALÉRIA (Phytotaxa, 2023)
Udotea is an exclusively marine green macroalgal genus with wide distribution in both tropical and subtropical regions. Due to the difficulty in properly delimiting infrageneric taxa based on morpho-anatomical characteristics by the presence of cryptic species and phenotypic plasticity, the use of techniques of DNA barcode and phylogenetic analysis have been fundamental to assess the Udotea species diversity. Information concerning this genus in Brazil is currently restricted to a few publications in checklists and/or regional floristic surveys along the tropical coast. This study aimed to evaluate the diversity of Udotea in northeastern Brazil through morphological-based taxonomy allied with plastid molecular markers, tufA and rbcL. We generated phylogenies of Udotea sensu lato, and we used different species delimitation methods to assess the diversity among sequences of selected tufA clades within Udotea sensu stricto. None of the eight infrageneric taxa reported for Brazil based only on morphology were confirmed by using molecular data. Udotea dotyi was revealed by tufA and rbcL sequences and represents its first occurrence for the western south Atlantic Ocean. A taxon named here as ‘Udotea cyathiformis’ requires further studies for its definition. This first molecular study on Udotea from the Brazilian coast shows that a broader sampling will be necessary to assess the true diversity of the genus in the western south Atlantic, which may be overestimated due to its high morphological plasticity.